NITRIC OXIDE - MARKER OF OXIDATIVE STRESS IN DIFFERENT TYPES OF FIXED DENTAL RESTAURATIONS - Florin Ciprian Badea; Mircea Grigorian; Cătălina Bănuţ; Gheorghe Raftu; Aureliana Caraiane (Romanian Society of Oral Rehabilitation, 2023)
The aim of the present study is to evaluate the level of oxidative stress by quantifying salivary Nitric Oxide in patients with three types of fixed prosthetic: porcelain fused to metal crown; all ceramic; zirconium ceramic. Material and Method. The study was performed on 50 subjects, divided in three groups for each type of fixed dental restauration. Nitric oxide was evaluated by the immunochromatographic method (Nitric Oxide Saliva Test Strips, Berkeley, USA) before and after the permanent cementation of the three different fixed prosthetic. Results.The highest values of Nitric Oxide were quantified in the patients group with porcelain fused to metal crown, after seven days and after six months with statistically significant differences between this values (p=0.0006); there are less statistical significance regarding the values of the same determinations in patients with all ceramics (p=0.02) and no statistically differences regarding the values of these determinations in patients with zirconium ceramic (p=0.32 ). Also, there are statistically significant differences regarding Nitric Oxide values in patients with porcelain fused to metal crown and those with all-ceramic (p=0.0001) and zirconium-ceramic (p=0.0007) after six months demonstrating that the highest level of oxidative stress is produced by metal-ceramic prosthetic materials. Conclusions. The evaluation of the Nitric Oxide level can be used to assess the intensity of oxidative stress in the oral cavity of patients rehabilitated orally with prosthetic works made of different materials.